Aesthetic aspects in meaning making - an explorative study of dance education in a PETE programme - Suzanne Lundvall; Ninitha Maivorsdotter (Stockholm University Press, 2010)
The article focuses on how aesthetic aspects of experience are involved in meaning making within an educational setting of body movement practice. The study explores stories of how physical education student teachers feel when participating in a dance lesson, with attention given to aesthetic aspects of embodied experiences in relation to meaning making. The study draws on Dewey's theory of experimental learning. Aesthetic experience is defined as the feeling of wholeness or fulfilment in the transaction taking place. The categorical analysis of content, inspired by pragmatic epistemology analyses, uses the operational concepts of gaps, encounters, and relations. Three categories of stories emerge linked by the resemblance of positive or negative feelings expressed. The aesthetic experiences seem to inform the students of the purpose of what is undertaken, how to value the experience, and how the meaning of the embodied experience is perceived.